2020
DOI: 10.34172/mejdd.2020.178
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Clinical Symptoms and Lab Tests with Endoscopic Severity Indexes in Patients with Inflammatory Bowel Diseases

Abstract: BACKGROUND The Crohn’s Disease Endoscopic Index of Severity (CDEIS) and the Ulcerative Colitis Endoscopic Index of Severity (UCEIS) are two validated endoscopic scoring system to evaluate patients with inflammatory bowel diseases (IBD). We conducted this study to evaluate the correlation between clinical symptoms and lab tests with these indexes in patients with Crohn’s disease (CD) and ulcerative colitis (UC). METHODS In this analytical study, 373 consecutive patients referred to Shahid Mohammadi Hospital wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, elevated fecal calprotectin was positively associated with inflammatory biomarkers, namely ESR and CRP [ 51 ]. Higher fecal calprotectin and the presence of mucus in diarrhea are known as significant predictors of the development of Crohn’s disease and disease activity [ 57 , 58 , 59 ]. In the multivariate analyses, only monocyte count and fecal calprotectin were associated with relapse [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, elevated fecal calprotectin was positively associated with inflammatory biomarkers, namely ESR and CRP [ 51 ]. Higher fecal calprotectin and the presence of mucus in diarrhea are known as significant predictors of the development of Crohn’s disease and disease activity [ 57 , 58 , 59 ]. In the multivariate analyses, only monocyte count and fecal calprotectin were associated with relapse [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 Missing info: Some information was not available in the electronic health record and therefore could not be included in the final descriptive analysis. 3 Other non-gastrointestinal irAEs included: dermatologic (10), endocrine (8), musculoskeletal (7), hepatic (3), neurologic (2), renal (1), and pulmonary (1) toxicity.…”
Section: Baseline Patient Characteristicsmentioning
confidence: 99%
“…Studies suggest that an estimated 15% of patients lack the ability to mount an elevated quantity of CRP due to genetic variations 1 , 2 . Its use, though nonspecific, has been shown to correlate with severity of inflammatory bowel diseases (IBD) as assessed endoscopically 3 . A meta-analysis suggested that CRP has a relatively high specificity (92%), but lower sensitivity (49%), to predict endoscopic activity in patients with known IBD, and normal CRP level does not exclude the possibility of active disease 4 .…”
Section: Introductionmentioning
confidence: 99%